From genotype to phenotype: can systems biology be used to predict Staphylococcus aureus virulence? - Priest, N; Rudkin, J; Feil, E; van den Elsen, J; Cheung, A; Peacock, S; Laabei, M; Lucks, D; Recker, M; Massey, R (2012)
With the advent of high-throughput whole-genome sequencing, it is now possible to sequence a bacterial genome in a matter of hours. However, although the presence or absence of a particular gene can be determined, we do not yet have the tools to extract information about the true virulence potential of an organism from sequence data alone. Here, we focus on the important human pathogen Staphylococcus aureus and present a framework for the construction of a broad systems biology-based tool that could be used to predict virulence phenotypes from S. aureus genomic sequences using existing technology.